Post-cholecystectomy clip migration—a unique method of retrieval. Issue 6 (30th June 2022) - Aaron, Ezekiel; Palamuthusingam, Pranavan
Abstract: Post-cholecystectomy clip migration with formation of bile duct stones is a known but rare complication of laparoscopic cholecystectomy. This report discusses the case of a 64-year-old lady who presented with biliary colic symptoms 12 years post laparoscopic cholecystectomy. Computed tomography of the abdomen demonstrated one surgical clip located in the distal common bile duct, with a bile stone formed around it. This was removed via ERCP with spyglass cholangioscopy and lithotripsy.